Analysis of Variation Characteristics and Driving Factors of Precipitation Isotopes in the Monsoon Region of Offshore China—A Case Study of Hong Kong - Liu Jiaxin (E3S Web of Conferences, 2023)
To explore the isotopic composition of precipitation in the monsoon region of offshore China, this paper takes Hong Kong, China as the study area. Based on the Global Network of Isotope in Precipitation (GNIP), the data about hydrogen and oxygen stable isotopes in the precipitation of Hong Kong from 1961 to 2022 were collected, from which its time variation trend was obtained via linear regression. Further, the distribution characteristics and influencing factors of hydrogen and oxygen stable isotopes in the precipitation of Hong Kong were analyzed. According to the results, the precipitation isotopes and d-excess in Hong Kong have no significant inter-annual variability. The seasonal variation of precipitation isotope and d-excess is monthly apparent, both of which are lower in the rainy season and higher in the dry season. In addition, the seasonal periodicity of isotope and d-excess proves that the main source of precipitation is marine water vapor, and the source of water vapor controlling precipitation in Hong Kong remains stable as a whole. The global meteoric water line in Hong Kong is δD=8.17δ18O+11.82, which is very close to the global one. Meanwhile, δ18O in precipitation is negatively correlated with the temperature, precipitation, and water vapor pressure. As the main driving force to control its isotope variation, precipitation conceals the effect of temperature. Taking Hong Kong as an example, the above research reveals some characteristics of monsoon regions in offshore China, which is of positive significance for further investigating the influencing factors of the hydrologic cycle and isotope change at regional and local scales in the future.